Radial Evolution of a CIR: Observations From a Nearly Radially Aligned Event Between Parker Solar Probe and STEREO‐A. Issue 3 (1st February 2021) - Allen, R. C.; Ho, G. C.; Mason, G. M.; Li, G.; Jian, L. K.; Vines, S. K.; Schwadron, N. A.; Joyce, C. J.; Bale, S. D.; Bonnell, J. W.; Case, A. W.; Christian, E. R.; et al.
Abstract: The addition of Parker Solar Probe (PSP) to the Heliophysics System Observatory has allowed for the unprecedented ability to study Corotating Interaction Regions (CIRs) at multiple radial distances without significant temporal/longitudinal variations. On September 19, 2019, PSP observed a CIR at ∼0.5 au when it was nearly radially aligned with the Solar Terrestrial Relations Observatory‐Ahead (STEREO‐A) spacecraft at ∼1 au, allowing for an unambiguous assessment of the radial evolution of a single CIR. Bulk plasma and magnetic field signatures of the CIR evolve in a fashion characteristic to previous observations; however, the suprathermal ions are enhanced over a larger longitudinal range at PSP than at STEREO‐A, although at much lower intensities. The longitudinal spread appears to be largely a consequence of magnetic field line topology at CIRs between the compressed slow solar wind upstream and high‐speed stream following the CIR, underscoring the importance of the large‐scale topology of these structures. Key Points: A CIR was observed by PSP and STA when the spacecraft were near radially aligned The plasma measurements suggest only radial evolution has occurred between observations Differences in fast and slow solar wind magnetic topology lead to a wider longitudinal extent of the suprathermal ion enhancement at PSP